Optimization of a siRNA Carrier Modified with a pH-Sensitive Cationic Lipid and a Cyclic RGD Peptide for Efficiently Targeting Tumor Endothelial Cells - Tomoya Hada; Yu Sakurai; Hideyoshi Harashima (MDPI AG, 2015)
In recent years, anti-angiogenic therapy has attracted much interest because it is a versatile approach to treating most types of tumors, and therefore would be expected to be applicable for various cancers. Severe adverse events in patients treated with currently available anti-angiogenic therapeutics have, however, been reported, and these are caused by their inhibitory effects in normal tissue. To achieve an efficient anti-angiogenic therapy with minimal toxicity, a drug delivery system (DDS) specific to tumor endothelial cells (TECs) is needed. Cyclic RGD (cRGD) is a well-known ligand against αVβ3 integrin that is expressed at high levels in the cell surface of TECs. To address this issue, we previously developed a cyclic RGD-equipped liposomal DDS (RGD-MEND) in which small interfering RNA (siRNA) was encapsulated. However, in the previous study, details of the preparation steps were not thoroughly examined. In this paper, to produce the most efficient delivery of therapeutic TECs, we explored optimum preparation conditions and components of the RGD-MEND. The cellular uptake and silencing ability of the RGD-MEND were investigated as a function of ligand density, poly(ethyleneglycol) linker length, and lipid composition. As a result, a knockdown efficiency that was five-fold higher than that of the previously reported one (ED50, from 4.0 to 0.75 mg/kg) was achieved.